Research and application of new enviromental-frendly technology without using chemicals for extraction of chitin from shrim shells - Thiet, Nguyen Van; Luong, Nguyen Ngoc; Quy Mai, Tran Thi; Hang, Hoa Thi; Thu, Nguyen Xuan; Phong, Nguyen Ngoc (Academia Journal of Biology, 2013)
Vietnam has a huge amount of rich-protein shrimp shells, containing chitin, a biological polymer that has many potential applications in different areas of life. However, this shrimp by-products are processed mainly by alkali-acid method, causing environmental pollution and can not recovery the protein in the starting material. For the first time in Vietnam, we have carried out research and successfully applied electrochemical technology to extract and purify the chitin from shrimp shells. This is a new technology for chitin extraction, that do not use alkali and acid as in the other chemical methods, so it is very friendly to the environment. The electrolysis is performed on the model device of size of 6 ´ 10 ´ 16.7 cm (with a capacity of 1 liter) at different NaCl concentrations in 90 minutes. After electrolytic extraction of chitin on the device the highest pH value of catolite solution is 12.43 at a concentration of 4% NaCl, and the lowest pH of anolite is 1.95 at NaCl concentrations of 1%. From the results of measuring the pH value of the electrode solutions and determination of protein extracted in the electrode cells were determined the optimal electrolyte concentration (that is 1% of NaCl) and minimal time (that is 1.0 - 1.5 hours) in DC current of 400 A/m2. Chitin preparations obtained by electrochemical technology have high purity, white or yellowish-white colour, no foreign odors, virtually no protein, with low mineral residues (< 0.4%) and average viscosimetric molecular weight from 240 to 1000 kDa.